Fostering fifth graders’ reading comprehension through the use of intensive reading in physical science - Bogoya González, Alethia Paola (Colombian Applied Linguistics Journal, 2011)
Reading comprehension in a content area needs to be seen from both the content and language perspectives. This paper examines the use of intensive reading, a strategy taken from the language teaching field, to help students improve their reading comprehension ability and develop understanding of science concepts. The study was carried out in a fifth grade class at a private bilingual institution of Bogotá. Reading was analyzed using a mixed-method approach that utilizes both qualitative and quantitative methods. The first method was done through students’ interviews, artefacts, and a teacher’s journal, and the second by means of two reading tests, Cloze and CARI, Content Area Reading Inventory Test. The statistical analysis shows that students improved their reading comprehension ability as their scores for the post-test were higher than those of the pre-test; this increment is statistically significant as p ≤ .05 when applying a t-test. The qualitative analysis shows that structured reading practices lead to the development of students’ cognitive processes. Overall, the results indicate that reading in science should be seen as dynamic process that incorporates learners’ strategies in order to develop conceptual understanding.